Introduction: The Brazilian Atlantic Forest1 - Morellato, L. Patricia C.; Haddad, Célio F. B. (Biotropica, 2000)
ABSTRACT The year 2000 marks 500 years of massive destruction for the Brazilian Atlantic Forest, as a consequence of the European colonization of Brazil. Today, the Atlantic Forest is restricted to ca 98,800 km2 of remnants, or 7.6 percent of its original extension. The Atlantic Forest continues to suffer under severe anthropogenic pressure, risking imminent extinction of the remaining species. Our current knowledge indicates that this complex biome contains a species diversity higher than most of the Amazon forests, and also has high levels of endemism. The 13 selected articles in this special issue present data on the natural history, ecology, sustainable management, and conservation of the Atlantic Forest. These articles represent a sample of the research conducted to date in the region and suggest avenues of future research, particularly with regard to conservation alternatives for the remaining portions of the Atlantic Forest. This special issue represents one of the first general references pertaining to the Brazilian Atlantic Forest. RESUMO O ano 2000 marca 500 anos de intensa destrul¸ão da Mata Atlãntica, como conseqüência da coloniza¸ão européia no Brasil. Hoje, a Mata Atlãntica está restrita a aproximadamente 98.000 km2 de remanescentes, ou 7,6% de sua extensão original, e os últimos remanescentes de floresta ainda encontram‐se sob intensa pressão antrópica e risco iminente de extin¸ão. De acordo com o nível atual de conhecimento, este bioma complexo contem maior diversidade de espécies que a maioria das forma¸ões florestais amazõnicas, bem como níveis elevados de endemismo. Os treze artigos selecionados para este fascícule especial apresentam dados sobre história natural, ecologia, manejo sustentado e conserva¸ão da Mata Atlãntica. Estes artigos representam uma amostragem das pesquisas realizadas na região, sugerindo possibilidades de estudos futures e discutindo alternativas para a conserva¸ão. Este fascículo especial corresponde a uma das primeiras referências gerais sobre a Mata Atlãntica brasileira.